Simultaneous voltammetric determination of Brilliant Blue FCF and Tartrazine for food quality control - Lipskikh, Olga I; Korotkova, Elena I; Barek, Jiri; Vyskocil, Vlastimil; Saqib, Muhammad; Khristunova, Ekaterina P (Talanta, 2020)
Voltammetric determination of Tartrazine (Tz) and Brilliant Blue FCF (BB) in their mixture using novel type of carbon black-polyethylene composite electrode (CBPCE) with renewable surface modified by carbon ink (CI) was developed. Electrochemical properties of the tested dyes were investigated in 0.1 mol L-1 Britton-Robinson (BR) buffer by cyclic voltammetry (CV) and linear scan voltammetry (LSV). Simultaneous determination of the dyes is based on the application of supporting electrolytes with different pH: 2.0 for Tz and 10.0 for BB. Under the optimum experimental conditions, linear concentration dependences in the concentration ranges from 0.037 to 1.38 μmol L-1 for Tz and from 0.025 to 2.52 μmol L-1 for BB were obtained by LSV in the first-order derivative mode. Limits of detection (LODs) for Tz and BB were 0.019 and 0.011 μmol L-1, respectively. The modified electrode showed good stability and reproducibility and was successfully applied for the determination of the mixture Tz and BB in a candy and soft drink products.